Effect of the minimal intervention protocol in the prevention of intraventricular hemorrhage in the premature infant (Colombia Medica, 1994)
A quasi-experimental study was done to identify the effect of the mínimum handling protocol in decreasing intraventricular hemorrhage among premature babies in the Intensive Care Unit of the Hospital Universitario del Valle. The sample was 31 babies in each group. The experimental group had a greater degree of severe asphyxia and was in intermittent mandatory ventilation. Nevertheless, there was no intraventricular hemorrhage in this group diagnosed by ultrasonography. The incidence of hemorrhage among the control babies was 13%. The differences were not statistically significant ( p = 0.05 ). Caring for premature children with the minimal handling protocol is an inexpensive technology appropriate for all neonate intensive care units. This approach improves children's quality of life by preventing intraventricular hemorrhage.